Analisis Komunikasi Digital Dalam Pembelajaran Daring Di Fakultas Psikologi UMBY - Wayan Wirayana; Muhammad Dhino Ridho; Sirajudin Halid (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the role of digital communication in online learning at the Faculty of Psychology, Mercu Buana University Yogyakarta (UMBY). The advancement of technology and changes in the education system due to the COVID-19 pandemic have driven the massive use of digital platforms in teaching and learning processes. Digital communication has become a key instrument in bridging interactions between lecturers and students. This research employs a descriptive qualitative approach, involving lecturers and students as the main subjects. The results indicate that the effectiveness of digital communication is influenced by levels of digital literacy, quality of interaction, clarity in delivering material, and technological support. The main challenges encountered include limited connectivity, insufficient ability to use digital platforms, and constraints in conveying non-verbal expressions. These findings are expected to provide recommendations for enhancing the quality of online learning, particularly in the context of effective and inclusive digital communication.